Erratum: Bioecological aspects of the common black field cricket, Gryllus assimilis (Orthoptera: Gryllidae) in the laboratory and in Eucalyptus (Myrtaceae) plantations (Journal of Orthoptera Research (2020) 29:1 (83-89) DOI: 10.3897/jor.29.48966) - Masson, Marcus Vinicius; de Souza Tavares, Wagner; Alves, Jacyr Mesquita; Ferreira-Filho, Pedro José; Barbosa, Leonardo Rodrigues; Wilcken, Carlos Frederico [UNESP]; Zanuncio, José Cola (Pensoft Publishers, 2020)
Although this article refers to the species under study as Gryllus assimilis, given the evidence presented, we cannot be certain of this identification. G. assimilis is a species that cannot reliably be identified based on morphology alone (Weissman and Gray 2019). For example, there are many species of Gryllus in Mexico with morphological characters similar to G. assimilis but with notably different calling songs (Weissman et al. 2009). The species of Gryllus in Brazil have not specifically been investigated, but, based on the diversity of Brazilian habitats, there are likely to be several species of Gryllus there (Weissman and Gray 2009). Without presenting a sonogram, characters of the file, and comparing DNA barcodes of cytochrome oxidase I (COI) with those in Weissman and Gray (2009), we cannot be certain that the species in question is in fact G. assimilis.